Pengaruh Kualitas Pelayanan Islami Terhadap Kepuasan dan Loyalitas Nasabah Bank BRI Syariah Surabaya - Putra, Rizky Pratama; Herianingrum, Sri (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to determine the influence of the Islamic service quality on customer satisfaction and loyalty switching intentions moderated by religious knowledge level in in Customer of BRISyariah Bank in Surabaya.The research method used is quantitative approach. This research use a total of 96 customers of BRISyariah Surabaya. Customer characteristics used are Moslem, registered as a funding or deposit customer for at least a year. The sampling technique is purposive sampling. This research uses a method PLS (Partial Least Square).The results showed that Islamic service quality has a positive and significant impact on customer satisfaction. Other results showed that customer satisfaction has significant impact to customer loyalty and Islamic service quality has significant effect on customer loyalty. This results in accordance with the theory of Othman and Owen that CARTER could be used to measure the quality of service on Islamic Banking. Suggestion for the BRISyariah Bank in Surabaya should maintain and improve its service quality in order to improve satisfaction and form a loyal customer. For further research, can be done by adding another variable which affect customer satisfaction and loyalty.